Octreotide in Intestinal Lymphangiectasia: Lack of a Clinical Response and Failure to Alter Lymphatic Function in a Guinea Pig Model - S Makhija; P-Y vod der Weid; J Meddings; SJ Urbanski; PL Beck (Canadian Journal of Gastroenterology)
Intestinal lymphangiectasia, which can be classified as primary or secondary, is an unusual cause of protein-losing enteropathy. The main clinical features include edema, fat malabsorption, lymphopenia and hypoalbuminemia. Clinical management generally includes a low-fat diet and supplementation with medium chain triglycerides. A small number of recent reports advocate the use of octreotide in intestinal lymphangiectasia. It is unclear why octreotide was used in these studies; although octreotide can alter splanchnic blood flow and intestinal motility, its actions on lymphatic function has never been investigated. A case of a patient with intestinal lymphangiectasia who required a shunt procedure after failing medium chain triglycerides and octreotide therapy is presented. During the management of this case, all existing literature on intestinal lymphangiectasia and all the known actions of octreotide were reviewed. Because some of the case reports suggested that octreotide may improve the clinical course of intestinal lymphangiectasia by altering lymphatic function, a series of experiments were undertaken to assess this. In an established guinea pig model, the role of octreotide in lymphatic function was examined. In this model system, the mesenteric lymphatic vessels responded to 5-hydroxytryptamine with a decrease in constriction frequency, while histamine administration markedly increased lymphatic constriction frequency. Octreotide failed to produce any change in lymphatic function when a wide range of concentrations were applied to the mesenteric lymphatic vessel preparation. In conclusion, in this case, octreotide failed to induce a clinical response and laboratory studies showed that octreotide did not alter lymphatic function. Thus, the mechanisms by which octreotide induced clinical responses in the cases reported elsewhere in the literature remain unclear, but the present study suggests that it does not appear to act via increasing lymphatic pumping.